Proposed new value proposition for pt besari wahana raya to acquire infrastructure development project in rural area - van der Muur, Averino; Rustiadi, Sonny (The Indonesian Journal of Business Administration, 2018)
Abstract - PT. Besari Wahana Raya is a contractor company whose expertise is in construction area and was established in 1999. PT. Besari Wahana Raya specialises itself as a contractor for the military. The company currently serves only one client, which is the Indonesia Air Force. PT. Besari Wahana Raya has been working with the same client for almost 20 years. The head quarter of the company is located in Duren Sawit, East Jakarta. After working with the same client for almost 20 years, the board of directors begin to realize that they can actually acquire another market segment. After 20 years doing business in the industry, PT. Besari Wahana Raya is planning to acquire a new market segment. Using all the capabilities of the company, PT. Besari Wahana Raya needs to offer a new value proposition for the new client. The new value proposition is local empowerment. By offering this new value proposition, PT. Besari Wahana Raya is able to acquire the new-targeted segment.  In order to complete the company’s purpose, an implementation plan has been developed in order to predict all the possibilities. By developing an implementation plan, PT. Besari Wahana Raya will be able to follow all the steps required to complete the goal. Keywords: Construction Company, Business issue, Local empowerment, Implementation plan